Ultra-sensitive troponin-I and incident coronary heart disease, stroke, heart failure, cardiac arrhythmias, arterial aneurysms and venous thromboembolism hospitalizations. (3rd October 2022) - Empana, J P; Lerner, I; Perier, M C; Jabre, P; Andrieu, M; Climie, R E; Van Sloten, T; Vedie, B; Geromin, D; Marijon, E; Danchin, N; Thomas, F; et al.
Abstract: Background: Cardiac troponin I (cTnI) as measured by high-sensitive assays has been related to incident cardiovascular disease events (CVD) in the community. With the advent of ultra-sensitive assays, it is now possible to detect troponin I at very low concentration, far below the classical threshold of 1.9 pg/mL. However, the clinical relevance of these low concentrations for predicting CVD is largely unknown. Purpose: To examine the association of cTnI as low as 0.013 pg/mL with incident cardiovascular disease events (CVDs) in the primary prevention setting. Methods: cTnI was analyzed in the baseline plasma (2008–2012) of CVD free volunteers from the Paris Prospective Study III using for the first time a novel ultra-sensitive immunoassay (Simoa Troponin-I 2.0 Kit, Quanterix, Lexington) with a limit of detection (LOD) of 0.013 pg/mL. Incident CVD hospitalizations for coronary heart disease, stroke, arrhythmias, venous thromboembolism, arterial aneurysms and heart failure were validated by critical review of the hospital records. Hazard ratios were estimated per log-transformed standard deviation (SD) increase of cTnI in Cox models using age as the time scale. The added value (gain in discriminatory capacity) of cTnI for CVD risk prediction was examined by calculating the Harell's C-index boostraped difference of the SCORE 2 risk model with and without cTnI. Results: There were 9503 CVD free participants (40% women) aged 59.6 (6.3) years at baseline. cTnI was detected in 99.6% of the participants (median value = 0.63 pg/mL, interquartile range [IQR] 0.39–1.09). After a median follow-up of 8.34 years (IQR, 8.0–10.07), 516 participants suffered 612 events. In fully-adjusted analysis, higher cTnI (per 1 SD increase of log cTnI) was significantly associated with CVD events combined (n=516, HR= 1.21; 1.06; 1.39). In univariate Cox analysis and compared to each single established risk factor, cTnI had the highest discrimination capacity for incident CVD events (C-index=0.6349) (Figure 1). Adding log cTnI to the SCORE 2 algorithm increased significantly albeit moderately discriminatory capacity (C-index 0.698 vs. 0.685; boostraped C index difference: 0.0135 (95% CI: 0.0131; 0.0138)). Conclusion: cTnI concentrations as measured by a novel ultra-sensitive immunoassay is associated with a significant increased risk of incident CVD events in the primary prevention setting. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): ANR: French National Research AgencyEurope: Horizon 2020